A very simple one-pot electrosynthesis of nitrones starting from nitro and aldehyde components. Issue 9 (5th April 2018) - Rodrigo, Eduardo; Waldvogel, Siegfried R.
Abstract : Very selective, sustainable and simple electro-conversion of nitroarenes with aldehydes into nitrones. Abstract : The cathodic treatment of nitroarenes in the presence of aldehydes yields directly and selectively nitrones. Electrolysis can be conducted on a very simple undivided beaker-type cell under constant current conditions. The conversion tolerates multiple bonds, a variety of functional groups and heterocyclic moieties. Competing reductive conversions such as pinacolization are not observed. The green aspects of this electro-conversion are avoidance of metals, an environmentally benign solvent mixture, and stable as well as sustainable carbon electrodes.